Properties of bricks with installation of bamboo fiber - Mohd Khairul Anuar Mat Kupli (School of Environmental Engineering, University Malaysia Perlis, 2012)
The sand bricks are usually used extensively in the construction industry as a wall panel, part of the construction of drains and so on. Basically, sand bricks are using cement and normal sand such as ordinary Portland cement and river sand. In addition, the sand bricks also must have its own mix ratio for enabling the content to be a piece of bricks. Usually, the use of river sand in our country is very widespread in the construction industry. Therefore, an alternative to use of river sand can be replaced with other materials to protect the environment of the river as well as prevent erosion and flooding. By using the bamboo fiber is one of the alternatives in the investigation of the sand bricks. River sand will be replaced with the bamboo fiber in accordance with a specified percentage. The percentage of the bamboo fiber to replace with the river sand is 1%, 3%, 5%, 7%, and 10%. In addition, a size of sand bricks was determined in this study, the size using is 225 mm x 115 mm x 70 mm. The sand bricks are placed at the air curing for 7 days and 28 days before compression strength test. Bamboo fiber brick was tested water absorption and density. These testing conducted to identify the strength of new sand bricks which produced for to compare with standard bricks. Apart from that, it is making for ensure this Bamboo Fiber brick production to reduce costs or be environmental friendly to user. The final result, shown that by using the bamboo fiber as replacing material with sand with ratio 1:3 have a difference between the standard sand brick. Based on the results, showed that when less than 3 percent of bamboo fiber is replaced into the sand brick compressive strength values that can be borne between 3 MPa to 5 MPa. It can be classified as non-load bearing brick in accordance with ASTM C129 standard. Meanwhile, if the bamboo fiber used, it increased more than 3 percent it would require improvements to the design to ensure that the standards achieved.